P01.043 Is surgical resection useful in elderly newly diagnosed glioblastoma patients? Outcome evaluation and prognostic factors assesment. (19th September 2018) - Pessina, F; Navarria, P; Conti Nibali, M; Riva, M; Carta, G; Clerici, E; Simonelli, M; Rudà, R; Scorsetti, M; Bello, L
Abstract: Background: The incidence of glioblastoma among elderly patients is constantly increasing. The value of radiation therapy and concurrent/adjuvant chemotherapy has been widely assessed. So far, the role of surgery has not been thoroughly investigated. The study aimed to evaluate safety and impact of several entities of surgical resection on outcome of elderly patients with newly diagnosed glioblastoma treated by a multimodal approach. Material and Methods: Patients ≥65 years, underwent surgery were included. The extent of surgical resection (EOR) was defined as complete resection (CR=100%), gross total resection (GTR=90%-99%), sub-total resection (STR=78%-90%), partial resection (PR=30%-78%), and biopsy. After surgery, all patients received adjuvant radiotherapy (60Gy/2Gy fraction) with concomitant/adjuvant temozolomide chemotherapy. Results: From March 2004 to December 2015, 178 elderly with a median age of 71 years (range 65–83 years) were treated. CR was obtained in 8 (4.5%), GTR in 63 (35.4%), STR in 46 (25.8%), PR in 16 (9.0%), and biopsy in 45 (25.3%). RT was started in all patients, concurrent/adjuvant CHT in 149 (83.7%) and 132 (74.2%). The median follow up time was 12.2 months (range 0.4–50.4 months). The median, 1, 2-year progression free survival were 8.9 months (95%CI 7.8–100. months), 32.0 ± 3.5%, and 12.9 ± 2.6%. The median, 1, 2-year overall survival were 12.2 (95%CI 11.3–13.1 months), 51.1 ± 3.7%, and 16.3 ± 2.9%. Tumor location, extent of resection and neurological status after surgery statistically affected survival (p<<0.01). Conclusion: Maximal surgical resection is safe and feasible also in elderly patients with influence on survival. A preoperative evaluation have to be carried out.